Analysis of Ultra Low Genome Conservation in Clostridium difficile - Scaria, Joy (Public Library of Science, 2010)

(untitled)
Microarray-based comparative genome hybridisations (CGH) and genome sequencing of Clostridium difficile isolates have shown that the genomes of this species are highly variable. To further characterize their genome variation, we employed integration of data from CGH, genome sequencing and putative cellular pathways. Transcontinental strain comparison using CGH data confirmed the emergence of a human-specific hypervirulent cluster. However, there was no correlation between total toxin production and hypervirulent phenotype, indicating the possibility of involvement of additional factors towards hypervirulence. Calculation of C. difficile core and pan genome size using CGH and sequence data estimated that the core genome is composed of 947 to 1,033 genes and a pan genome comprised of 9,640 genes. The reconstruction, annotation and analysis of cellular pathways revealed highly conserved pathways despite large genome variation. However, few pathways such as tetrahydrofolate biosynthesis were found to be variable and could be contributing to adaptation towards virulence such as antibiotic resistance.